EKSTRAKSI MINYAK ATSIRI KULIT JERUK MANIS DENGAN METODE VACUUM MICROWAVE ASISSTED HYDRODISTILLATION - Megawati, Megawati; kurniawan, rosa dwi (Semarang State University, 2015)
The objective of this research is to extract essential oil of sweet orange peel (Citrus sinensis) using vacuum microwave assisted hydrodistillation (VMAHD) method. The operation condition was at various orange peel mass (50, 100, and 150 g) and extraction times (2, 4, 6, 8, and 10 min). The volume of water as solvent was about 300 mL. Before extraction, analysis of oil content in orange peel was conducted using solvent extraction by soxhlet method with 100 mL of n-hexane and 20 cycles number. The analysis resulted in the oils of sweet orange peel is about 3.2% v/w. Effect of extraction in vacuum conditions is studied by comparing the result of extraction in vacuum pressure to extraction at atmospheric pressure. The boiling temperature in atmospheric pressure was 80 oC and in vacuum pressure decreased to 50 oC. Thus oil yield in vacuum pressure is greater than at atmospheric pressure for 8 min of time. The experimental data showed that the oil yield is influenced by time; the longer time of extraction, oil yield obtained tends to be increased. In the materialâs mass variation, oil yield tends to be decreased in percentage with increasing mass of material. The VMAHD method results on the oil content of 0.22% v/w yield obtained materials, test oil density of 0.84 g / mL, and essential oil dissolved in alcohol 70%. GC-MS analysis indicates that orange peel oil is composed of Limonene (96.69%), and Pinene (3.31%), which are in the class of sesquiterpenes